Efficacy of Upfront Docetaxel With Androgen Deprivation Therapy for Castration-Sensitive Metastatic Prostate Cancer Among Minority Patients. (July 2021) - Pathak, Surabhi; Thekkekara, Romy; Yadav, Udit; Ahmed, Ahmed Tarig; Yim, Barbara; Lad, Thomas E.; Mullane, Michael; Batra, Kumar Kunnal; Aronow, Wilbert S.; Psutka, Sarah P.
Abstract : Background: Upfront docetaxel (UD) with androgen deprivation therapy (ADT) has been demonstrated to improve survival outcomes in metastatic castration-sensitive prostate cancer (mCSPC). However, existing studies have included predominantly Caucasian patients. Study Question: To compare the efficacy of addition of UD to ADT in mCSPC to ADT alone among minority patients. Study Design: Retrospective study of mCSPC patients. Measures and Outcomes: Patients treated with UD and ADT between January 2014 and December 2017 (UD + ADT, n = 44) were compared with those treated with ADT alone between January 2008 and January 2017 (ADT, n = 38); patients of Caucasian ethnicity were excluded. The outcome of interest was progression-free survival (PFS), which was estimated using Kaplan–Meier analysis and Cox proportional hazard analysis. Results: Overall, 63 (76.8%) patients were African American and 16 (19.5%) were Hispanic. Fifty-five (67%) patients had high-volume mCSPC. The median follow-up was 14 months [95% confidence interval (CI): 10.4–16.5] for UD + ADT and 42 months (95% CI: 17–66.9) for ADT. Median PFS did not differ between groups: UD + ADT: 16 versus ADT: 18 months [hazard ratio (HR) for UD + ADT = 0.88, 95% CI: 0.48–1.62; P = 0.70]. In patients with high-volume disease, median PFS remained similar (UD + ADT: 16 vs. ADT: 14 months (HR for UD + ADT = 0.64, 95% CI: 0.33–1.25; P = 0.19). On multivariable analysis, prolonged time to nadir PSA, HR = 0.83 (95% CI: 0.76–0.90), was independently associated with PFS. The most common toxicities in UD + ADT were anemia and fatigue. Major limitations include small sample size and potential for selection bias due to the retrospective study design. Conclusions: In this retrospective review of a minority mCSPC cohort, UD + ADT was not associated with improved PFS compared with ADT alone. Although further study with larger sample size is needed, these results underscore the importance of ensuring accrual of minorities in clinical trials, reflective of the real-world setting.